2019
DOI: 10.1080/09658416.2019.1620756
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of L1 form-meaning mappings can reduce crosslinguistic effects in L2 grammatical learning

Abstract: The present study examined the extent to which first language (L1) awareness can benefit second language (L2) grammatical learning of the French Imparfait, a crosslinguistically complex target feature. Sixty-nine English-speaking learners of L2 French received different types of explicit information about L2 or L2 + L1 form-meaning mappings. A 'core' treatment received by all learners consisted of EI about L2 with L2 comprehension-based practice of French sentences. Two further treatments examined the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…Blom & Paradis, 2015;Ebert et al, 2014;Łockiewicz & Jaskulska, 2016;Tribushinina et al, 2020), it seems likely that both aspects of our method (explicitness and raising cross-linguistic awareness) have contributed to the positive results. Our findings converge with recent research demonstrating that pedagogical approaches relying on cross-linguistic comparisons and activating learner's entire linguistic repertoire enhance metalinguistic awareness and lead to greater learning gains in an L2 (Kupferborg & Olshtain, 1996;Leonet et al, 2020;Lucas, 2020;McManus, 2019;McManus & Marsden, 2017. Whereas these prior studies have focused on the development of L2 grammar, our research demonstrates that cross-linguistic approaches are also effective in teaching L2 spelling.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Blom & Paradis, 2015;Ebert et al, 2014;Łockiewicz & Jaskulska, 2016;Tribushinina et al, 2020), it seems likely that both aspects of our method (explicitness and raising cross-linguistic awareness) have contributed to the positive results. Our findings converge with recent research demonstrating that pedagogical approaches relying on cross-linguistic comparisons and activating learner's entire linguistic repertoire enhance metalinguistic awareness and lead to greater learning gains in an L2 (Kupferborg & Olshtain, 1996;Leonet et al, 2020;Lucas, 2020;McManus, 2019;McManus & Marsden, 2017. Whereas these prior studies have focused on the development of L2 grammar, our research demonstrates that cross-linguistic approaches are also effective in teaching L2 spelling.…”
Section: Discussionsupporting
confidence: 88%
“…Siu & Ho, 2015;Sparks, 2016;Sparks et al, 2009;Van de Ven et al, 2018;Zeguers et al, 2018), there is also recent evidence suggesting that learners rarely engage in explicit comparisons of L1 and L2 (Bell et al, 2020), and they are often unaware of crucial cross-linguistic differences (Ammar et al, 2010). Therefore, it has been suggested that L2 teachers should use contrastive pedagogical approaches explicitly comparing L1 and L2 grammar (Bell et al, 2020;Lightbown & Spada, 2000;McManus, 2019).…”
Section: L1 Transfer In Developmental Dyslexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Initial study: McManus and Marsden (2017) Background: McManus and Marsden (2017) investigated the extent to which explicit instruction about L2 and L1 was beneficial for the L2 learning of the French Imparfait, a grammatical aspect form well-documented to late-acquired due to complex L1-L2 differences in terms of viewpoint aspect form-meaning mappings (Howard, 2005;Kihlstedt, 2015). McManus and Marsden (2017) hypothesized that increasing learners' sensitivity to L1-L2 differences could be one way to facilitate L2 learning (see also McManus, 2019McManus, , 2021a). The instruction included (i) explicit information (EI) about aspect forms and (ii) comprehension practice of aspect forms in sentences.…”
Section: Exemplar Close Replication Study: Mcmanus and Marsden (2018)mentioning
confidence: 99%
“…The impact that the student's first language has on their learning and acquisition of any grammatical issue is, on the contrary, a well known fact, as it is the basic hypothesis underlying the pedagogical dimension of Contrastive Analysis (Fries 1945;Lado 1957). However, as it is presented in this volume, it sheds new light on such premise for two main reasons: first, because its connection with the acquisition of TAM in second languages has not been deeply studied (but see Collins 2002;Izquierdo & Collins, 2008;McManus, 2019;Nishi & Shirai, 2019;Slabakova, 2000, among others); and secondly, as a consequence, because the first and second languages it correlates (Russian/Spanish, Dutch/Spanish, Catalan/English, among others) have not been deeply examined from this perspective within this field.…”
Section: Sla Findings and Language Teachingmentioning
confidence: 99%